Improvement of Wind Farm with PMSG using STATCOM - Mutharasan A; Rajesh R; Rameshkumar T; Dharmaraj M.; Chandrasekar P (Institute of Advanced Engineering and Science, 2016)
This paper studies about the dynamic performance of the Permanent Magnet Synchronous Generator with Static Synchronous Compensator (STATCOM) for Wind farm integration. A whole dynamic model of wind energy conversion system (WECS) with PMSG and STATCOM are established in a MATLAB environment. With this model the dynamic behaviour of the generator and the overall system has been studied to determine the performance of them with and without STATCOM. Final results portrays that the WECS based PMSG with STATCOM improves the transient response of the wind farm when the system is in fault.